Respuesta :
Rearrange the ODE as
[tex]\dfrac{\mathrm dy}{\mathrm dx}+x\sin2y=x^3\cos^2y[/tex]
[tex]\sec^2y\dfrac{\mathrm dy}{\mathrm dx}+x\sin2y\sec^2y=x^3[/tex]
Take [tex]u=\tan y[/tex], so that [tex]\dfrac{\mathrm du}{\mathrm dx}=\sec^2y\dfrac{\mathrm dy}{\mathrm dx}[/tex].
Supposing that [tex]|y|<\dfrac\pi2[/tex], we have [tex]\tan^{-1}u=y[/tex], from which it follows that
[tex]\sin2y=2\sin y\cos y=2\dfrac u{\sqrt{u^2+1}}\dfrac1{\sqrt{u^2+1}}=\dfrac{2u}{u^2+1}[/tex]
[tex]\sec^2y=1+\tan^2y=1+u^2[/tex]
So we can write the ODE as
[tex]\dfrac{\mathrm du}{\mathrm dx}+2xu=x^3[/tex]
which is linear in [tex]u[/tex]. Multiplying both sides by [tex]e^{x^2}[/tex], we have
[tex]e^{x^2}\dfrac{\mathrm du}{\mathrm dx}+2xe^{x^2}u=x^3e^{x^2}[/tex]
[tex]\dfrac{\mathrm d}{\mathrm dx}\bigg[e^{x^2}u\bigg]=x^3e^{x^2}[/tex]
Integrate both sides with respect to [tex]x[/tex]:
[tex]\displaystyle\int\frac{\mathrm d}{\mathrm dx}\bigg[e^{x^2}u\bigg]\,\mathrm dx=\int x^3e^{x^2}\,\mathrm dx[/tex]
[tex]e^{x^2}u=\displaystyle\int x^3e^{x^2}\,\mathrm dx[/tex]
Substitute [tex]t=x^2[/tex], so that [tex]\mathrm dt=2x\,\mathrm dx[/tex]. Then
[tex]\displaystyle\int x^3e^{x^2}\,\mathrm dx=\frac12\int 2xx^2e^{x^2}\,\mathrm dx=\frac12\int te^t\,\mathrm dt[/tex]
Integrate the right hand side by parts using
[tex]f=t\implies\mathrm df=\mathrm dt[/tex]
[tex]\mathrm dg=e^t\,\mathrm dt\implies g=e^t[/tex]
[tex]\displaystyle\frac12\int te^t\,\mathrm dt=\frac12\left(te^t-\int e^t\,\mathrm dt\right)[/tex]
You should end up with
[tex]e^{x^2}u=\dfrac12e^{x^2}(x^2-1)+C[/tex]
[tex]u=\dfrac{x^2-1}2+Ce^{-x^2}[/tex]
[tex]\tan y=\dfrac{x^2-1}2+Ce^{-x^2}[/tex]
and provided that we restrict [tex]|y|<\dfrac\pi2[/tex], we can write
[tex]y=\tan^{-1}\left(\dfrac{x^2-1}2+Ce^{-x^2}\right)[/tex]
[tex]\dfrac{\mathrm dy}{\mathrm dx}+x\sin2y=x^3\cos^2y[/tex]
[tex]\sec^2y\dfrac{\mathrm dy}{\mathrm dx}+x\sin2y\sec^2y=x^3[/tex]
Take [tex]u=\tan y[/tex], so that [tex]\dfrac{\mathrm du}{\mathrm dx}=\sec^2y\dfrac{\mathrm dy}{\mathrm dx}[/tex].
Supposing that [tex]|y|<\dfrac\pi2[/tex], we have [tex]\tan^{-1}u=y[/tex], from which it follows that
[tex]\sin2y=2\sin y\cos y=2\dfrac u{\sqrt{u^2+1}}\dfrac1{\sqrt{u^2+1}}=\dfrac{2u}{u^2+1}[/tex]
[tex]\sec^2y=1+\tan^2y=1+u^2[/tex]
So we can write the ODE as
[tex]\dfrac{\mathrm du}{\mathrm dx}+2xu=x^3[/tex]
which is linear in [tex]u[/tex]. Multiplying both sides by [tex]e^{x^2}[/tex], we have
[tex]e^{x^2}\dfrac{\mathrm du}{\mathrm dx}+2xe^{x^2}u=x^3e^{x^2}[/tex]
[tex]\dfrac{\mathrm d}{\mathrm dx}\bigg[e^{x^2}u\bigg]=x^3e^{x^2}[/tex]
Integrate both sides with respect to [tex]x[/tex]:
[tex]\displaystyle\int\frac{\mathrm d}{\mathrm dx}\bigg[e^{x^2}u\bigg]\,\mathrm dx=\int x^3e^{x^2}\,\mathrm dx[/tex]
[tex]e^{x^2}u=\displaystyle\int x^3e^{x^2}\,\mathrm dx[/tex]
Substitute [tex]t=x^2[/tex], so that [tex]\mathrm dt=2x\,\mathrm dx[/tex]. Then
[tex]\displaystyle\int x^3e^{x^2}\,\mathrm dx=\frac12\int 2xx^2e^{x^2}\,\mathrm dx=\frac12\int te^t\,\mathrm dt[/tex]
Integrate the right hand side by parts using
[tex]f=t\implies\mathrm df=\mathrm dt[/tex]
[tex]\mathrm dg=e^t\,\mathrm dt\implies g=e^t[/tex]
[tex]\displaystyle\frac12\int te^t\,\mathrm dt=\frac12\left(te^t-\int e^t\,\mathrm dt\right)[/tex]
You should end up with
[tex]e^{x^2}u=\dfrac12e^{x^2}(x^2-1)+C[/tex]
[tex]u=\dfrac{x^2-1}2+Ce^{-x^2}[/tex]
[tex]\tan y=\dfrac{x^2-1}2+Ce^{-x^2}[/tex]
and provided that we restrict [tex]|y|<\dfrac\pi2[/tex], we can write
[tex]y=\tan^{-1}\left(\dfrac{x^2-1}2+Ce^{-x^2}\right)[/tex]